Flouting Maxims by Indonesia Presidential Candidates in Najwa Shihab’s Talk Show - Vivin Agustin; Sri Minda Murni; Fauziah Khairani Lubis (Randwick International of Education and Linguistics Science Journal, 2024)
This study investigates the flouting of conversational maxims by Prabowo Subianto and Gibran Rakabuming Raka in the "13 Tahun Mata Najwa: Bergerak Bergerak Berdampak" episode of the Mata Najwa talk show. By analyzing the dialogues of Prabowo Subianto and Gibran Rakabuming Raka, the research aims to understand the strategies and reasons behind the flouting of Grice's maxims in a high-stakes political context. Using Grice's Cooperative Principle as a framework, the research identifies and analyzes instances where the maxims of quantity, quality, relevance, and manner are flouted. The analysis reveals that Gibran and Prabowo using strategies such as ambiguity, sarcasm, and metaphor are also used. Notably, Gibran is identified as the more frequent flouter of maxims compared to Prabowo. This study contributes to a deeper understanding of political communication and the strategic use of language in media interactions.